Knowledge search versus knowledge deployment: How foreignness can be both an asset and a liability for firms - Jörg Zimmermann; Wolfgang Sofka (European Commission, Joint Research Centre (JRC), 2013)
Many modern firms compete globally. However, research into whether foreignness is an asset or a liability in competition with domestic firms is inconclusive. We argue that foreign MNC subsidiaries are not per se advantaged or disadvantaged. We suggest that the distinction originates from the nature of the subsidiary's activity in the host country. We focus on two activities: knowledge search and knowledge deployment. We predict theoretically that domestic firms have advantages when they search for knowledge due to their embeddedness in the host country. However, this increased embeddedness reduces the degree of novelty of their knowledge pool. Foreign MNC subsidiaries therefore have advantages in knowledge deployment because they draw from a richer, international knowledge pool. However, these advantages accrue to both foreign and domestic MNCs. We test and support these predictions for a longitudinal dataset of 2900 firm observations in Spain. We develop recommendations for research and practice based on these findings.
Keywords: F23; A14; C23; L15; 330; Liability of foreignness; foreignness as an asset; knowledge search; deployment